Efficacy of Early Combination Therapy With Lianhuaqingwen and Arbidol in Moderate and Severe COVID-19 Patients: A Retrospective Cohort Study - Fang, Jie; Li, Hui; Du, Wei; Yu, Ping; Guan, Ying-Yun; Ma, Shi-Yu; Liu, Dong; Chen, Wei; Shi, Guo-Chao; Bian, Xiao-Lan (Frontiers in Pharmacology, 2020)
Objective Since the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Wuhan City, China, coronavirus disease 2019 (COVID-19) has become a global pandemic. However, no special therapeutic drugs have been identified for COVID-19. The aim of this study was to search for drugs to effectively treat COVID-19. Materials and Methods We conducted a retrospective cohort study with a total of 162 adult inpatients (≥18 years old) from Ruijin Hospital (Shanghai, China) and Tongji Hospital (Wuhan, China) between January 27, 2020, and March 10, 2020. The enrolled COVID-19 patients were first divided into the Lianhuaqingwen (LHQW) monotherapy group and the LHQW + Arbidol combination therapy group. Then, these two groups were further classified into moderate and severe groups according to the clinical classification of COVID-19. Results The early combined usage of LHQW and Arbidol can significantly accelerate the recovery of patients with moderate COVID-19 by reducing the time to conversion to nucleic acid negativity, the time to chest CT improvement, and the length of hospital stay. However, no benefit was observed in severe COVID-19 patients treated with the combination of LHQW + Arbidol. In this study, both Arbidol and LHQW were well tolerated without serious drug-associated adverse events. Conclusion The early combined usage of LHQW and Arbidol may accelerate recovery and improve the prognosis of patients with moderate COVID-19.